Pengaruh Worldview terhadap Pengambilan Keputusan dalam Kehidupan Sehari-hari - Mujahid, Kasori; Aziz, Nur; Al Faizi, Ahmad Akbar (TSAQOFAH, 2025)
Worldview serves as a cognitive framework that influences individual decision-making in daily life. This article examines the impact of various worldviews, such as religious, secular, and materialistic perspectives, on how individuals set priorities and make choices. The findings reveal that worldviews significantly shape thought patterns, justify actions, and determine the consequences of decisions. These insights highlight the importance of a well-grounded worldview in fostering responsible decision-making. This study employs a qualitative approach using in-depth interviews with 20 purposively selected respondents. Thematic analysis was conducted to explore the relationship between worldview and decision-making. Data triangulation was applied to ensure the validity of the findings.